TP53 codon 72 single nucleotide polymorphism in chronic lymphocytic leukemia - Bilous, N.I.; Abramenko, I.V.; Chumak, A.A.; Dyagil, I.S.; Martina, Z.V. (Experimental Oncology, 2014)
Defects in the tumor suppressor gene TP53 are known to be important in chronic lymphocytic leukemia (CLL) and TP53 inactivation is associated with a particularly aggressive form of the disease. The single nucleotide polymorphism in the TP53 gene at codon 72 (rs1042522), results in amino acid substitution influencing apoptotic potential of TP53 protein. The aim of the study was to evaluate the association of the TP53 codon 72 polymorphism and incidence of TP53 mutations in CLL patients. Methods: 261 CLL samples were analyzed by polymerase chain reaction and direct sequencing for TP53 mutations and single nucleotide polymorphism. Results: The 72Pro/Pro genotype was associated with an increased incidence of TP53 mutations in previously treated patients (OR = 2.503; 95% CI 1.142–5.487; р = 0.001). Conclusion: This study revealed that the TP53 codon 72 polymorphism may be used as a risk factor for incidence of TP53 mutations in CLL. Key Words: chronic lymphocytic leukemia, TP53 mutations, single nucleotide polymorphism.